Trade integration between Eastern and Western Europe: Politics follows the market - Daniel Piazolo (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
This paper examines to what extent Eastern Europe trade reorientation towards the West has been driven by market forces versus policies for regional integration. Hierarchical cluster analysis based on bilateral trade intensity reveals the convergence of regional trade structures to the pre-World-War II pattern. Estimates of the expected trade pattern of Eastern Europe with a gravity model predict continuing rising importance of the EU. Furthermore, the assessment of the welfare implications of preferential access to EU markets shows that beneficial effects of trade expansion are likely to outweigh possible distortions. Hence integration policies follow the facts created by the market.
Keywords: 330; Außenwirtschaft; Wirtschaftliche Anpassung; Gravitationsmodell; Osteuropa; Westliche Staaten